2021
DOI: 10.3390/molecules26082260
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Components in Oat and Barley Grain as a Promising Breeding Trend for Functional Food Production

Abstract: Cereal crops, such as oats and barley, possess a number of valuable properties that meet the requirements for functional diet components. This review summarized the available information about bioactive compounds of oat and barley grain. The results of studying the structure and physicochemical properties of the cell wall polysaccharides of barley and oat are presented. The main components of the flavonoids formation pathway are shown and data, concerning anthocyanins biosynthesis in various barley tissues, ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 89 publications
0
12
0
5
Order By: Relevance
“…Oat-based foods are beneficial for people with insulin-resistant forms of diabetes, hypertension, obesity, and dyslipidemia [ 15 ]. In addition, the safety of including oat in a gluten-free diet has been confirmed in long-term studies [ 15 , 16 , 17 ]. Thus, oat is a highly nutritious cereal crop suitable for curative, preventive, and functional nutrition [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oat-based foods are beneficial for people with insulin-resistant forms of diabetes, hypertension, obesity, and dyslipidemia [ 15 ]. In addition, the safety of including oat in a gluten-free diet has been confirmed in long-term studies [ 15 , 16 , 17 ]. Thus, oat is a highly nutritious cereal crop suitable for curative, preventive, and functional nutrition [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, two reviews have been reported indicating the nutritional benefits and features of oats. Shvachko and co-workers highlighted the importance of studying plant genetic resources and the biosynthetic processes of bioactive compounds in oats, which require consistent revision and improvement of methodological and technical approaches ( Shvachko et al, 2021 ). Paudel and co-workers summarized the potential health benefits of oats and their bioactive components regarding various diseases including cardiovascular diseases, type II diabetes, obesity, cancer, immunomodulation, antioxidant activity, gut health, inflammation, atherosclerosis, antimicrobial, dermatological disorder and celiac disease ( Paudel et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…These unsaturated fatty acids are associated with various beneficial physiological properties, such as the prevention of dementia and antioxidant activity [ 10 , 15 , 19 ]. Recently, unsaturated fatty acids were shown to lower blood cholesterol, leading to increased interest in oats as a functional food [ 20 , 21 , 22 ]. Oats also contain polyphenols including caffeic acids, coumaric acids, gallic acids, hydroxybenzoic acids, protocatechuic acids, syringic acids and vanillic acids as the bioactive compounds [ 2 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%